Kriteriji zapisovanja in redakcija slovstvene folklore pri nekaterih južnoslovanskih avtorjih - Stanonik, Marija (Otrok in knjiga, 1998)
The contribution presents a work of some of the most prominent South Slavonic collectors and writers of literary folklore. The authoress reminds us of frequent editorial interferences or improvements done by particular writers on a collected material
Keywords: Karadžić, Vuk Stefanivič; Šenoa, Avgust; ljudsko slovstvo; oral literature; folklora; južnoslovanski narodi